2016
DOI: 10.1002/jclp.22295
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Suicidal Ideation in College Students: The Mediating and Moderating Roles of Hopelessness, Alcohol Problems, and Social Support

Abstract: Social support may be a key variable for suicide prevention among college students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 53 publications
5
68
0
9
Order By: Relevance
“…Alcohol use has been found to be a significant risk factor for suicide ideation (Lamis et al 2016), attempts (Windle 2004), and completions (Kolves et al 2006). In a systematic review of research, there was consistent support for both individual-and population-level associations between alcohol use and suicidal behavior.…”
Section: Risk Factorsmentioning
confidence: 94%
“…Alcohol use has been found to be a significant risk factor for suicide ideation (Lamis et al 2016), attempts (Windle 2004), and completions (Kolves et al 2006). In a systematic review of research, there was consistent support for both individual-and population-level associations between alcohol use and suicidal behavior.…”
Section: Risk Factorsmentioning
confidence: 94%
“…Although the association between depression and suicidal risk has been confirmed in many studies, others have argued that the influence of depression on suicidal risk might be indirect (e.g., Campos et al., ; Jahn, Cukrowicz, Linton, & Prabhu, ; Lamis, Ballard, May, & Dvorak, ; Rhodes & Bethell, ; Vanderwerker et al., ). The interpersonal–psychological theory of suicidal behavior (IPTS; Joiner, ; Van Orden et al., 2010) provides an important perspective to understand the mechanism underlying this association.…”
Section: Depression and Suicidal Riskmentioning
confidence: 96%
“…Additionally, social support can also influence suicide by moderating other variables associated with suicide (Lamis et al . ; Panagioti et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that people who perceive less support are more likely to feel depressed and contemplate suicide (Smith et al 2016). Additionally, social support can also influence suicide by moderating other variables associated with suicide (Lamis et al 2016;Panagioti et al 2014). The moderating role of social support on suicide may be better understood through the stress-buffering model, in which social support can serve as a coping resource to moderate the relationship between stressors and negative psychological reactions (Kwok et al 2011).…”
Section: Introductionmentioning
confidence: 99%